PENGARUH TERPAAN ADVERGAME DI DALAM GAME ONLINE CALL OF DUTY MOBILE TERHADAP KEPUTUSAN PEMBELIAN (Survei Anggota Grup Facebook [Official] Garena Call of Duty Mobile Indonesia) - Irsyad Harisandy (2023)
In this era of globalization, technology continues to develop rapidly until now, so does the game industry. Game is a medium of entertainment that is available to everyone and everyone, and can be used to entertain or eliminate boredom. This research is motivated by the influence of advergame exposure in the online game Call of Duty Mobile on purchasing decisions. This study intends to determine how much influence advergame exposure has in the online game Call of Duty Mobile on purchasing decisions. This research uses a descriptive quantitative research approach. Researchers used data collection techniques in the form of questionnaires to 100 respondents to obtain data. The results of the study show that there is an effect of Advergame Exposure (X) on Purchase Decision (Y) of 21.5% and the remaining 78.5% is determined by other factors not examined, such as events that are held offline, the existence of e-sport tournaments and advertisements that appear on various platforms, ranging from YouTube, Facebook, Instagram, and Tiktok. It can be concluded that Advergame Exposure (X) has a positive and significant effect on Purchase Decision (Y).